1989
DOI: 10.1111/j.1600-0528.1989.tb00001.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of dental services among Danish youths: role of the social environment, the individual, and the delivery system

Abstract: The purpose of the present study was to analyze the separate effect and the total effect of the social environment, the individual and the delivery system on frequency of use of dental services among youths. The variables of use were divided into the three main groups according to Coleman (12). Information concerning use of dental services, individual and structural variables was obtained by a self-administered questionnaire to 756 Danes 20-21 yr old in 1984-85. Information concerning social environmental vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…It is very rare internationally and in health care generally to have no socioeconomic differences in the utilization of health care services. Usually, predisposing, enabling and need faetors at-e associated with dental visits (36) and thet-efot-e soeioeconomic diffet-ences in the use of dental care have been very clear (25,30,(37)(38)(39), However, school dental care with an organized system of recall has been shown to reduce these differences (15,23), Equality in dental cat-e seetns to have been aehieved vet-y well in Finland since 1985. Equity has also been approached, because the national statistics show that almost all the ehildt-en examined have also been tt-eated aecording to their individual preventive and restorative treatment need as determined by a health center dentist (7).…”
Section: Discussionmentioning
confidence: 99%
“…It is very rare internationally and in health care generally to have no socioeconomic differences in the utilization of health care services. Usually, predisposing, enabling and need faetors at-e associated with dental visits (36) and thet-efot-e soeioeconomic diffet-ences in the use of dental care have been very clear (25,30,(37)(38)(39), However, school dental care with an organized system of recall has been shown to reduce these differences (15,23), Equality in dental cat-e seetns to have been aehieved vet-y well in Finland since 1985. Equity has also been approached, because the national statistics show that almost all the ehildt-en examined have also been tt-eated aecording to their individual preventive and restorative treatment need as determined by a health center dentist (7).…”
Section: Discussionmentioning
confidence: 99%
“…However, one of the items,`d uring the last 5 yr I have forgotten to go to a dental appointment'', showed fair reliability and validity. Also previous research has indicated that forgetting appointments is a common behavior, or one of the adolescents' most prevalent excuses towards themselves and others for their non-attendance behavior (16). This item was therefore included as one of the independent variables in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study among adolescents in Norway, 16.4% of them had missed or cancelled more than 20% of their dental appointments during the age period from 12±18 yr. Dental anxiety seemed to be the major reason for 38% of them (2).…”
mentioning
confidence: 98%
“…The relationship between dental anxiety and irregular dental attendance and avoidance of dental care is well established [7-10], and also the differences by gender and age, with higher prevalence of dental anxiety in women than in men [2]. Dental attendance is influenced by socioeconomic variables [11-13], while the relationship between those factors and dental anxiety is more unclear [4]. …”
Section: Introductionmentioning
confidence: 99%